n Numeries-taksomiese evaluering van die takson acacia karoo hayne in Suidelike Afrika - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1982.